Sustainability Research in Quantum Optics: Defining the Role of Compressed Matter Physics - Oscar, Schersclight; Xavier, Embrechts; Mark, Elladdadi (Journal of Tecnologia Quantica, 2024)
Quantum Optics, as a field that studies the interaction between light and matter at the quantum level, has the potential to reveal new phenomena in the physics of compressed matter. Compressed matter, often encountered in extreme conditions like stellar or planetary cores, is key to understanding fundamental physical processes and advanced technological applications. This research aims to explore and define the role of compressed matter physics in the context of sustainability. By examining how materials behave under extreme pressure and temperature, we seek to identify ways Quantum Optics can facilitate the development of new environmentally friendly materials and energy-efficient technologies. The methodology used involves a combination of Quantum Optics experiments and theoretical modelling. Experiments include using high-intensity lasers and ion traps to create compressed conditions. In contrast, theoretical models are used to predict the behaviour of the material and its effects on energy efficiency and sustainability. Results from experiments and theoretical models show that Quantum Optics techniques can be effectively used to control and manipulate compressed matter, providing new data on its mechanical and electronic properties. These findings suggest that exploiting the physics of compressed matter can play an important role in developing sustainable technologies. The conclusion of this research is to strengthen the position of Quantum Optics as a vital tool in sustainability research. Through Quantum Optics, the physics of compressed matter offers an uncharted path for innovation in sustainable materials and technologies. Further research is recommended to explore the practical application of these findings in industrial and environmental contexts.